Answer:
(x + 1)/4x² + 4(x + 1)/4x²
Step-by-step explanation:
x+1/4x² + x+1/x²
The above can be simply as follow:
Find the least common multiple (LCM) of 4x² and x². The result is 4x²
Now Divide the LCM by the denominator of each term and multiply the result with the numerator as show below:
(4x² ÷ 4x²) × (x + 1) = x + 1
(4x² ÷ x²) × (x + 1) = 4(x + 1)
x+1/4x² + x+1/x² = [(x + 1) + 4(x + 1)]/ 4x²
= (x + 1)/4x² + 4(x + 1)/4x²
Therefore,
x+1/4x² + x+1/x² = (x + 1)/4x² + 4(x + 1)/4x²
Answer:
12in is you answer
Step-by-step explanation:
The formula to find circumference is ![C=2\pi r](https://tex.z-dn.net/?f=C%3D2%5Cpi%20r)
so to rearrange to solve for radius that will be ![r=\frac{C}{2\pi }](https://tex.z-dn.net/?f=r%3D%5Cfrac%7BC%7D%7B2%5Cpi%20%7D)
=![\frac{75}{2\pi }](https://tex.z-dn.net/?f=%5Cfrac%7B75%7D%7B2%5Cpi%20%7D)
=11.94in
V=π * r^2 * h/3 = π * 2^2 * 8/3 ≈ 33.51032 or about 34 units^2
Answers:
The formula is [f(-1)-f(-4)]/[3]
The value of f(-1) is 3
The value of f(-4) is -3
The average rate of change is 2
==============================================
Explanation:
For the first blank, we use the formula
[ f(b) - f(a) ]/[ b - a ]
where 'a' and 'b' are the endpoints for the x interval
In this case, a = -4 and b = -1. When you plug those values into the formula above, you get...
[ f(b) - f(a) ]/[ b - a]
[ f(-1) - f(-4)]/[ -1 - (-4) ]
[ f(-1) - f(-4)]/[ -1+4 ]
[ f(-1) - f(-4)]/[ 3 ]
which is why the answer is choice C for the first blank
-------------------------------------------
To compute the value of f(-1), we draw a vertical line through -1 on the x axis. This vertical line crosses the diagonal function graph at the point (-1,3). The y value of this point is what we want. Plugging in x = -1 leads to y = 3. This is why f(-1) = 3
If you want, you can draw a horizontal line through (-1,3) and you'll see it touching 3 on the y axis.
-------------------------------------------
Follow similar steps as above to compute f(-4). Draw a vertical line through x = -4 on the x axis. Mark the point where the vertical line crosses the diagonal line. This point is (-4,-3). Optionally draw a horizontal line over til you hit the y axis and you'll find that y = -3 corresponds to x = -4
This is why f(-4) = -3
-------------------------------------------
We'll use the last three sections to compute the average rate of change. Everything combines together building up to this moment.
From the first part, we had the formula
[ f(b) - f(a) ]/[ b - a ]
[ f(-1) - f(-4)]/[ 3 ]
We can replace the "f(-1)" with 3 since we found that f(-1) = 3
Similarly, f(-4) = -3 so we can replace the "f(-4)" with -3
Doing those replacements and simplifying leads to...
[ f(-1) - f(-4)]/[ 3 ]
[ 3 - (-3)]/[ 3 ]
[ 3 + 3]/[ 3 ]
6/3
2
So the average rate of change is 2
Note: because the entire graph is a straight line, the average rate of change for any interval a < x < b is going to be equal to the slope m. In this case, the slope of the line is m = 2/1 = 2. We move up 2 units each time we move to the right 1 unit along the diagonal line.
Answer:
C
Step-by-step explanation:
The volume of a cone is given by ![V=\frac{1}{3}\pi r^2h](https://tex.z-dn.net/?f=V%3D%5Cfrac%7B1%7D%7B3%7D%5Cpi%20r%5E2h)
The volume of a cylinder is given by ![V=\pi r^2 h](https://tex.z-dn.net/?f=V%3D%5Cpi%20r%5E2%20h)
<em>Where h is the height and r is the radius</em>
The first figure is a cone with height 6 and radius 5, we can put it into the formula and find the volume:
![\frac{1}{3}\pi r^2 h\\\frac{1}{3}\pi (5)^2 (6)\\=157.08](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7B3%7D%5Cpi%20r%5E2%20h%5C%5C%5Cfrac%7B1%7D%7B3%7D%5Cpi%20%285%29%5E2%20%286%29%5C%5C%3D157.08)
The second figure is a cylinder with height 50 and radius 1, we can put it into the formula and find the volume:
![\pi r^2 h\\\pi (1)^2 (50)\\=157.08](https://tex.z-dn.net/?f=%5Cpi%20r%5E2%20h%5C%5C%5Cpi%20%281%29%5E2%20%2850%29%5C%5C%3D157.08)
We can see that they are equal. So answer choice C is right.